Diagnostic value of glutamate with 2-hydroxyglutarate in magnetic resonance spectroscopy for IDH1 mutant glioma. Issue 11 (5th May 2016) - Nagashima, Hiroaki; Tanaka, Kazuhiro; Sasayama, Takashi; Irino, Yasuhiro; Sato, Naoko; Takeuchi, Yukiko; Kyotani, Katsusuke; Mukasa, Akitake; Mizukawa, Katsu; Sakata, Junichi; Yamamoto, Yusuke; Hosoda, Kohkichi; et al.
Abstract: Background: Mutations in the isocitrate dehydrogenase 1 ( IDH1 ) gene that are frequently observed in low-grade glioma are strongly associated with the accumulation of 2-hydroxyglutarate (2HG), which is a valuable diagnostic and prognostic biomarker of IDH1 mutant glioma. However, conventional MR spectroscopy (MRS)–based noninvasive detection of 2HG is challenging. In this study, we aimed to determine the additional value of other metabolites in predicting IDH1 mutations with conventional MRS. Methods: Forty-seven patients with glioma underwent conventional single voxel short echo time MRS prior to surgery. A stereotactic navigation-guided operation was performed to resect tumor tissues in the center of the MRS voxel. MRS-based measurements of metabolites were validated with gas chromatography–mass spectrometry. We also conducted integrated analyses of glioma cell lines and clinical samples to examine the other metabolite levels and molecular findings in IDH1 mutant gliomas. Results: A metabolomic analysis demonstrated higher levels of 2HG in IDH1 mutant glioma cells and surgical tissues. Interestingly, glutamate levels were significantly decreased in IDH1 mutant gliomas. Through an analysis of metabolic enzyme genes in glutamine pathways, it was shown that the expressions of branched-chain amino acid transaminase 1 were reduced and glutamate dehydrogenase levels were elevated in IDH1 mutant gliomas. Conventional MRS detection of glutamate and 2HG resulted in a high diagnostic accuracy (sensitivity 72%, specificity 96%) for IDH1 mutant glioma. Conclusions: IDH1 mutations alter glutamate metabolism. Combining glutamate levels optimizes the 2HG-based monitoring of IDH1 mutations via MRS and represents a reliable clinical application for diagnosing IDH1 mutant gliomas.